Hydrostatic Release Unit (HRU) By Adding Water Sensor - Fatihin Syahmi Ahmad Shukri,; Ibrahim, Siti Aida (Progress in Engineering Application and Technology, 2022)
Self-rescue devices are essential in an emergency, and one of the self- rescue devices is a life raft. However, the rescue raft has a problem in automatic launching using the Hydrostatic Release Unit (HRU). HRU is the one of the components where it needed to release life raft automatically when emergency happens. Unfortunately, the effectiveness of the HRU is questionable because several studies are stating that the HRU cannot function. These because the component that being used in HRU mostly a steel where the pin is attach with the spring and make it tight to release the spring. One of other things is, HRU can be function when it reaches 1.5m until 4m unless it has an enough pressure that exerted on the HRU, if not the diaphragm cannot be uprise and release pin from spring. Therefore, this study aimed to fabricate a prototype of HRU that use water sensor. This study uses several components such as Arduino, water sensor and servo motor. The programming c++ being used in this project to make servo motor and water sensor work automatically. There were 3 specimens that being used as a testing to ensure that this product work nicely which is thread, rubber band and fishing line.